Students' Attitudes towards Memes in Writing Report Text - Ariani, Nora; Emeliya Sukma Dara Damanik (Universitas Cokroaminoto Palopo, 2024)
The objective of this study is to investigate how students' attitudes in writing report texts by using meme media as well as the reasons that led to certain attitudes that occurred. The research design used was descriptive qualitative. The participants in this study were 32 students of the class IX superior of SMP 1 Muhammadiyah Medan who were selected using the purposive sampling technique. There are two ways of data collection techniques used, there are questionnaires and interviews. While the data measurement scale used is Likert scale. The results showed that students' attitudes were positive towards the use of meme media in writing report texts. As for what causes students' positive attitudes, they feel happy, entertained, comfortable, and increase their interest in learning to write report texts. Most students are active consumers of popular culture, and memes are often part of popular culture. Therefore, the use of memes in learning to write helps students feel more connected to the learning material as it utilises cultural elements that are familiar to them. The results of this study shows that memes are effectively used to boost students' attitude in writing report texts. The researcher recommend teachers choose memes that are suitable for learning in order to create a comfortable and enjoyable learning atmosphere.